Mechanical strength of binary oil palm kernel shell and HZSM-5 zeolite fuel pellets - Lai, Zhenyue; Goh, S. (Elsevier Ltd, 2015)
Oil palm kernel shell fuel pellets for gasification may be improved by incorporating a catalyst with the ability to eliminate tar and increase gas yield. However, the pelletization of palm kernel shell with a catalyst constituent into a binary pellet had varying effects on the properties of the final densified product. In this study, the influence of compaction pressure on the strength of binary oil palm kernel shell and HZSM-5 zeolite fuel pellets was determined. It was observed that the porosity of the binary pellet increased with the volume fraction of HZSM-5 zeolite in the mixture, resulting in weaker pellets. The average elastic rebound of the binary pellets increased as the composition of zeolite in the binary mixture increases. The pellet strengths were found to increase with longer hold times during the compaction process. The effect of hold time diminished as the binary pellet approached its maximum strength and near-zero porosity. A new empirical model was developed and shown to be able to predict the strength of the binary mixture pellet based on the volume fraction of HZSM-5 zeolite in the binary pellet, hold time and elastic rebound.